Moringa oleifera Leaves Ethanol Extract Inhibits HT-29 Cells and COX-2 Expression Predictably Through PPARγ Activation - Tedjo, Aryo; Aprilliyani, Ifana; Kusmardi, Kusmardi; Megawati, Ajeng; Noor, Dimas Ramadhian (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Colorectal cancer is the second leading cause of death among all cancer cases worldwide. Cancer cells often exhibit overexpression of cyclooxygenase-2 (COX-2), producing prostaglandin E2 (PEG2) and subsequent inflammation and neoplasia. Moringa oleifera is rich in bioactive compounds such as polyphenols, flavonoids, and saponins, known for their anti-inflammatory and antioxidant properties. This study aimed to investigate the inhibitory effects of M. oleifera leaves ethanol extract on COX-2 expression in HT-29 cells. Dried M. oleifera leaves (5 g) were ethanol-macerated for 24 hours, yielding a 10 mg ethanol extract. MTT inhibition is used for immunocytochemistry evaluation of COX-2 expression. Molecular docking of phenolic compounds from the extract on PPARγ indicated an agonistic potential. The ethanol extract of M. oleifera leaves demonstrated anticancer activity with an IC50 value of 114.8 µg/ml, with a significant reduction in COX-2 expression observed at a dose of 100 ppm, resulting in an H-score of 111.83 ± 2.21. Peroxisome proliferator-activated receptor-gamma (PPARγ) activity is thought to be the first step in suppressing COX-2 expression. Three phenolic compounds found in M. oleifera are predicted to be PPARγ agonists: rutin, naringin, and hesperidin, according to the molecular docking simulations.